2011
DOI: 10.3354/ab00329
|View full text |Cite
|
Sign up to set email alerts
|

Benthic communities in relation to wave exposure and spatial positions on sublittoral boulders in the Baltic Sea

Abstract: Boulders are an important substrate for Baltic Sea benthic communities. Although previous studies have examined benthic species on sublittoral boulders in the Baltic Sea, information on benthic assemblages and how they vary in relation to structuring factors is limited. The aim of the present study was to describe the benthic communities, including both algae and animal taxa, on sublittoral boulders in relation to spatial positions on the boulders (4 levels) and differences in wave exposure (2 levels). The mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…The most frequent components of the brackish hydrolittoral assemblages, represented by barnacles and mussels (A. improvisus and Mytilus juv. ), have been observed in high biomass on exposed shores of the Baltic Sea (Wallin et al, 2011) and were considered to be the most frequent components of wave-exposed intertidal biotopes in the Northern Atlantic Ocean bioregion (Bartsch & Tittley, 2004). This confirms that A. improvisus is well adapted for survival in the highly hydrodynamic coastal rock belt of the Baltic Sea and is one of the dominant species in brackish communities.…”
Section: Discussionsupporting
confidence: 61%
“…The most frequent components of the brackish hydrolittoral assemblages, represented by barnacles and mussels (A. improvisus and Mytilus juv. ), have been observed in high biomass on exposed shores of the Baltic Sea (Wallin et al, 2011) and were considered to be the most frequent components of wave-exposed intertidal biotopes in the Northern Atlantic Ocean bioregion (Bartsch & Tittley, 2004). This confirms that A. improvisus is well adapted for survival in the highly hydrodynamic coastal rock belt of the Baltic Sea and is one of the dominant species in brackish communities.…”
Section: Discussionsupporting
confidence: 61%
“…From the results of this study and those of Grzelak and Kuklinski (2010) and Wallin et al (2011), it appears that there are no boulder habitat specialists in the species depauperate regions of the Baltic Sea (i.e. the regions occurring further east of the entrance and in south-west).…”
Section: Discussionmentioning
confidence: 88%
“…The hypotheses investigated in previous similar studies that included B. improvisus (Grzelak and Kuklinski, 2010;Wallin et al, 2011) concerned habitat suitability, with distributions of living animals being of interest. These studies reported large densities of B. improvisus tests, which were comparable to the total densities of empty + occupied tests we found, but they did not mention the presence of any empty tests.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent review by Crain et al (2008) of marine ecosystem studies found that the interaction of environmental temperature with stressors ranging from pH to disease to overfishing could be additive (effects reflect sum of individual stressors), synergistic (effect greater than sum of individual stressors) or antagonistic (overall effect less than sum of individual stress effects). Many of these observations likely resulted from differential impacts operating at different trophic levels (Crain et al (Jones et al 1995) M. edulis (Berge et al 2006;Bibby et al 2008;Bechmann et al 2011) M. galloprovincialis (Michaelidis et al 2005;Kurihara et al 2008) Salinity M. edulis (Bussell et al 2008;Deschaseaux et al 2011) M. galloprovincialis (Solic et al 2010;Gombac et al 2011) Wave exposure M. edulis (Carrington 2002;Carrington et al 2009;Wallin et al 2011) M. galloprovincialis (Pfaff et al 2011) M. californianus Petes et al 2008) Food availability and temperature M. galloprovincialis (Schneider et al 2010) M. trossulus (Schneider et al 2010) Food availability and wave exposure M. californianus (Dahlhoff & Menge 1996) Food availability, temperature and wave exposure M. californianus (Dahlhoff et al 2002) Metal bioaccumulation and temperature M. edulis…”
mentioning
confidence: 99%